(untitled) (Al-Qamar, 2022)
Some words are used as real or basic terms of Quran and the other ones are attributes. This research paper deals with dissimilarities between them. The names of the Holy Qur’an are personal pronouns, while the difference in the number and derivatives of the attributes is an argument that the attributes are ijtihad. In the same way, among the terms of the Holy Qur’an, the Qur’an is the only specific term which is used for the Book of Allah, while the rest of the names can be applied to other heavenly books in terms of general meaning. By considering the names and attributes of the Holy Qur’an, we come to know that each term or attribute has a different meaning, their goals and objectives are also different from each other but there are very few who’s cerebral is only from Sunnah.